A Pragmatic Analysis Of Personal Deixis In Iron LadyMovie Manuscript - Fatkhunurohmah, Novie Ima, Drs. Sigit Haryanto, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
This research paper aims at describing the types of personal deixis and finding the reference of personal deixis. The object to be analyzed is personal deixis in the form of words. The writer takes the data from Iron Lady movie manuscript. The type of the research is descriptive qualitative research and this research uses documentation method to get the data. In clarifying the types of personal deixis the writer uses pragmatics analysis especially deixis theory. In finding out the reference of personal deixis, the writer employs reported speech theory by Hurford and Brendan. Then, the technique of analyzing data are finding the types of personal deixis used in Iron Lady movie manuscript, describing the reference of the use of personal deixis in movie script of Iron Lady, drawing the conclusion and suggestion based on the data analysis. The research finding of the study shows that there are three types of personal deixis first personal deixis, second personal deixis and third personal deixis and three kinds of the reference on Iron Lady movie include that reference that refers to first person, the reference which refers to second person and the reference which refers to third person and the data of this research consists of 185 personal deixis.